Favourable outcomes for high‐risk Burkitt lymphoma patients (IPI 3‐5) treated with rituximab plus CODOX‐M/IVAC: Results of a phase 2 UK NCRI trial. Issue 1 (29th April 2020) - Phillips, Elizabeth H.; Burton, Catherine; Kirkwood, Amy A.; Barrans, Sharon; Lawrie, Anthony; Rule, Simon; Patmore, Russell; Pettengell, Ruth; Ardeshna, Kirit M.; Montoto, Silvia; Paneesha, Shankara; Clifton‐Hadley, Laura; et al.
Abstract: Introduction: Outcomes after frontline treatment of Burkitt lymphoma (BL) have improved with the introduction of dose‐intense chemotherapy regimens, such as CODOX‐M/IVAC. While rituximab has increased survival rates for most forms of high‐grade B‐cell lymphoma, there has previously been hesitancy about incorporating it into BL treatment, partly due to concerns about increased toxicity. Prospective data using the standard dose CODOX‐M/IVAC regimen in combination with rituximab are lacking. We conducted a single‐arm phase 2 trial to assess the efficacy and toxicity of R‐CODOX‐M/R‐IVAC. Methods: Eligible patients were aged 18–65 years, with newly diagnosed BL with MYC rearrangement as the sole cytogenetic abnormality, and high‐risk disease, defined by an International Prognostic Index (IPI) score of 3‐5. Patients received two cycles of R‐CODOX‐M chemotherapy alternating with two cycles of R‐IVAC, followed by two further cycles of rituximab alone. The primary endpoint was 2‐year progression‐free survival. Results: Thirty‐eight patients were registered but after central pathology review, 27 patients had confirmed BL and commenced study treatment. Median age was 35 years, 14.8% patients had central nervous system involvement and 18.5% were HIV positive. Twenty‐two (81.4%) patients completed four cycles of chemotherapy. There were two treatment‐related deaths (7.4%). Two‐year progression‐free and overall survival rates were 77.2% (90% confidence interval [CI]: 56.0‐89.0) and 80.7% (90% CI: 59.6‐91.5), respectively. Conclusions: This prospective trial demonstrates excellent survival rates with R‐CODOX‐M/R‐IVAC in a high‐risk BL cohort. It provides reassuring evidence regarding the feasibility of this regimen and also provides a benchmark for future studies.